The frontal gland in workers of Neotropical soldierless termites - Sobotník, Jan; Sillam-Dussès, David; Weyda, Frantisek; Dejean, Alain; Roisin, Yves; Hanus, Robert; Bourguignon, Thomas (Naturwissenschaften, 2010)
The presence of the frontal gland is well established in termite soldiers of Rhinotermitidae, Serritermitidae, and Termitidae. It is one of their main defensive adaptations or even an exclusive weapon. The gland was also occasionally reported in alate imagoes, but never in the worker caste. Here, we report the first observation of a frontal gland in workers of several Neotropical and one African species of Apicotermitinae. The ultrastructure of Aparatermes cingulatus and Anoplotermes nr. subterraneus is described in detail. In these two species, the gland is well-developed, functional and consists of class 1 secretory cells. The presence of envelope cells, wrapping the gland, is an unusual feature, as well as the presence of several zonulae adherens, connecting neighbouring glandular cells. The frontal gland of workers is homologous to this organ in soldiers and imagoes, as evidenced by the same position in the head and its connection to the same muscle. However, the defensive role of the frontal gland in workers remains to be confirmed.
Keywords: Francouzská Guyana; Brazílie; Endocrine Glands; zvířata; Isoptera; Bolívie; Paraguay; sociální chování; Surinam; French Guiana; Suriname; ekosystém; mikroskopie elektronová rastrovací; endokrinní žlázy; Ecosystem; Social Behavior; Brazil; Animals; Bolivia; Microscopy, Electron, Scanning